The politics of student mobility: Links between outbound student flows and the democratic development of post-Soviet Eurasia - Chankseliani, M (Elsevier, 2018)
The study offers new empirical material to link student mobility and the levels of attained democracy in the former Soviet countries. Theoretically-informed analysis of cross-sectional data shows that the former Soviet countries with higher proportions of students studying in Europe or the United States have achieved higher levels of democratic development. In contrast, countries with higher proportions of students studying in the most popular, authoritarian destination - Russia - have reached significantly lower levels of democratic development. The study uses ideas of democratic socialisation at universities as well as apprenticeships in democracy to advance the intellectual agenda of linking two fields - educational studies and political science.